Nearly half of adults with symptoms of sexually transmitted infections (STIs) did not seek clinical care: A population-based study of treatment-seeking behavior among adults in Rakai, Uganda. - Yasmin P Ogale; Caitlin E Kennedy; Fred Nalugoda; Josephine Mpagazi; Jade C Jackson; Ronald Galiwango; Robert Ssekubugu; Godfrey Kigozi; Julie A Denison; Charlotte A Gaydos; Joseph Kagaayi; M Kathryn Grabowski (PLOS Global Public Health)
Understanding treatment-seeking behavior is critical to the treatment and control of sexually transmitted infections (STIs), yet current data on STI treatment seeking in low-resource settings is rare. This population-based study aimed to describe STI treatment-seeking behavior and identify factors associated with seeking treatment at a clinic among adults with STI-related symptoms in rural Uganda. The STI prevalence study (STIPS) conducted a survey and STI testing among all consenting adults aged 18-49 in two communities in rural south-central Uganda. Of 1,825 participants, 962 individuals self-reported STI symptoms in the past six months; we present descriptive data on treatment seeking and STI prevalence among these individuals. We used multivariable Poisson regressions with robust variance to determine the sociodemographic and symptom-related factors independently associated with seeking STI treatment at a clinic and assessed the association with previous clinic treatment seeking and current STI diagnosis. Forty-three percent of adults who reported STI-related symptoms in the past six months said they did not seek any treatment. Among those who did, 58% sought treatment at a private clinic, 28% at a government clinic, 9% at a pharmacy/drug store, 3% at a traditional healer, 2% at a market/shop, and 5% at another location. Among both males and females, having multiple STI related symptoms was positively associated with clinic treatment seeking (males = PRR: 1.73, 95%CI: 1.36-2.21; females = PR: 1.41, 95%CI: 1.12-1.78). Approximately one-third of males and females who reported previously seeking clinic treatment for their symptoms were diagnosed with a curable STI at the time of the survey. In this setting, nearly half of adults with STI-related symptoms are not seeking clinical care and many who report having sought treatment for recent STI symptoms have curable STIs. Future studies should explore barriers to care-seeking and strategies to improve STI services.